Tunable two-dimensional array patterning of antibody annuli through microsphere templating - Wolf, C.; Li, Qin (American Chemical Society, 2010)
Protein microarrays are of great research interest because of their potential application as biosensors for high-throughput protein and pathogen screening technologies. In this active area, there is a lack of techniques that can result in annulus-shaped protein structures (e.g., for the utilization of curved surfaces for enhanced protein−protein interactions and the detection of antigens). We present a new technique employing colloidal templating to yield large-scale (∼cm2) 2D arrays of antibodies against Escherichia coli K12 and enhanced green fluorescent protein (eGFP) on a versatile glass surface. The antibodies are swept to reside around the templating microspheres during solution drying and physically adsorb onto the glass. After the microspheres are removed, an array of annulus-shaped antibody structures is formed. We demonstrate the preserved antibody structure and functionality by binding the specific antigens and secondary antibodies, respectively, which paves the way for the binding of biomolecules and pathogens such as bacteria and viruses. The structures were investigated via atomic force, confocal, and fluorescence microscopy. Operational factors such as the drying time, temperature, and humidity as well as the presence of surfactants in the antibody solution were tuned to obtain a stable antibody structure.